2019
DOI: 10.1002/cyto.a.23869
|View full text |Cite
|
Sign up to set email alerts
|

Yiqi Chutan Tang Reduces Gefitinib‐Induced Drug Resistance in Non‐Small‐Cell Lung Cancer by Targeting Apoptosis and Autophagy

Abstract: High incidence and mortality rates for non‐small‐cell lung cancer (NSCLC) lead to low survival rates. Epidermal growth factor receptor‐tyrosine kinase inhibitors (EGFR‐TKI) are commonly first prescribed for NSCLC patients with EGFR mutations. However, most patients with sensitizing EGFR mutations become resistant to EGFR‐TKI after 9–13 months treatment. Yiqi Chutan Tang (YQCT) has been prescribed as a treatment to this issue for over 20 years. In this report, high‐performance liquid chromatography (HPLC) analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Several studies have proved that gefitinib exerts anticancer activity in multiple types of human cancer, including non‐small cell lung cancer, and ESCC (Sasatani et al, 2019; Schueler et al, 2019; Zhang et al, 2019). But, the resistance to gefitinib treatment is a major obstacle to the effective treatment of patients with ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have proved that gefitinib exerts anticancer activity in multiple types of human cancer, including non‐small cell lung cancer, and ESCC (Sasatani et al, 2019; Schueler et al, 2019; Zhang et al, 2019). But, the resistance to gefitinib treatment is a major obstacle to the effective treatment of patients with ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…However, nearly all patients treated with gefitinib deteriorate due to the emergence of EGFR-TKI acquired resistance, for which no effective therapy is currently available (22,23). Emerging studies have reported that certain Chinese medicines could reduce gefitinib-induced drug resistance, including TP (24,25). However, the role and mechanism of TP in gefitinib-induced drug resistance in NSCLC is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The last article reports on drug actions immunomonitored by high-content FCM (15,16). Parry et al investigated long-term Ibrutinib therapy in B-Cell Chronic Lymphocytic Leukemia (CLL).…”
Section: Tumors Meng Et Al Link An Increased Cxcl10 Expression and mentioning
confidence: 99%
“…The last article reports on drug actions immunomonitored by high-content FCM ( 15 , 16 ). Parry et al.…”
mentioning
confidence: 99%